(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
In the present research paper an attempt has been made to introduce standard operating procedure (SOP) for preparation of Naga Bhasma described in Ayurvedic formulary of India (AFI) using traditional Puta method. A total 60 Putas were given, out which first 50 Puta were Ardha gajaputa, followed by last 10 Puta as Gajaputa. In this method Manahshila and Kanji were taken as media. Arddha Gaja Puta (burnt with 4 kg Cow dung cake) was given for first 50 puta and the last ten Putas was given Gajaputa (burnt with 8 kg cow dung cake). The percentage increase in the Naga bhasma prepared after 60 Puta was 12%. Upto 50 Puta the increase in weight of Naga was 208%, while in last 10 Putas the percentage of decrease in weight was 63.66%. The average percentage purity of Naga decreased from 93.18% to 81.44% after Shodhana. The percentage of (Pb) Lead in Naga Bhasma 50 Puta and 60 Puta were 14.118% and 14.872 % respectively. Chemically Naga Bhasma was found in the form of PbS form.